Perceptions, knowledge, and perceived competencies of South African speech-language therapists to render transgender voice and communication training - Van der Linde, Jeannie (University of Pretoria, 2024)
Dissertation (MA (Speech-Language Pathology))--University of Pretoria, 2023.